Lean Production Determinant Factors in Malaysia Paper Manufacturer Industry - Ibrahim, Irwan; Johan, Zaimy Johanna; Jamil, Norina Ahmad; Tarli, Siti Masithah Mohd; Amer, Afizan (International Journal of Supply Chain Management, 2019)
Nowadays, in daily operations have to alert about the lean production that would be effect of the whole of production management. Lean production is one of the main successful management in operations to keep maintain the organization reputation and its ready to compete the globally in manufacturing firm. The objective of lean production is to make the operation process become smoothly of processing items, reduced waste and successful in every target. However, many organizations fail to apply the lean concepts in their operations. Therefore, this study attempted to examine the relationship between lean production (LP) and three dimensions which are transportation, quality and communication. This study employed quantitative study using questionnaire. Data was collected from 45 employees that chosen by expertise in production and the data was analyzed using Statistical Package of Social Science (SPSS). This study hoped to make new understanding on the important to apply lean concept in production management.